European heart journal. Acute cardiovascular care - Vranckx, Pascal; European Society of Cardiology. Acute Cardiovascular Care Association (Oxford : Oxford University Press, 2021)
The official peer-reviewed journal of the Acute Cardiovascular Care Association (ACVC) of the European Society of Cardiology. This journal covers all aspects of acute cardiac care, including acute coronary syndromes, cardiogenic shock, cardiac arrest, cardiac arrhythmias and acute heart failure.
"Acute Cardiovascular Care Association"--Home page.
Description based on online resource; title from home page (viewed on October 13, 2020).
Keywords: Cardiac intensive care -- Periodicals